2020
DOI: 10.1002/jpen.2052
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Therapy Cost‐Effectiveness Model Indicating How Nutrition May Contribute to the Efficiency and Financial Sustainability of the Health Systems

Abstract: Background: Malnutrition is highly prevalent in hospitalized patients but seldom recognized and treated. Malnutrition poses several adverse events, such as increased infection rates, length of hospital stay, and mortality, as well as costs. Early nutrition interventions have been shown to decrease the associated malnutrition burdens, leading to relevant savings. Thus, this study aims to evaluate the cost-effectiveness of nutrition therapy, including oral supplements to at-risk or malnourished adult inpatients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 66 publications
0
9
0
2
Order By: Relevance
“…[20][21][22][23] By reducing LOS, lowering infection rates, and avoiding readmissions, early nutrition therapy targeting malnourished hospitalized patients suggests total healthcare cost savings. 16,24 In the ICU, appropriate nutrition management is vital to avoid potential risks. 25 Given the characteristics and comorbid conditions of our real-world sample, proper choice of high-protein EN is essential.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23] By reducing LOS, lowering infection rates, and avoiding readmissions, early nutrition therapy targeting malnourished hospitalized patients suggests total healthcare cost savings. 16,24 In the ICU, appropriate nutrition management is vital to avoid potential risks. 25 Given the characteristics and comorbid conditions of our real-world sample, proper choice of high-protein EN is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Effective cancer control programs and policies should therefore consider economic aspects for all cancer patients, survivors, and their carers [106][107][108][109][110][111]. A poor nutrition status is costly [106,112,113] and nutrition interventions contribute to reduced healthcare costs [112,[114][115][116][117]. On the other hand, the economic cost of malnutrition also impacts the healthcare system due to the costs associated with more complications, increased length of hospital stay (LOS), readmissions and increased morbidity [112].…”
Section: Integrating Nutrition Into Cancer Care Is Economically Advan...mentioning
confidence: 99%
“…Early provision of ONS to patients at risk for malnutrition is also expected to be costeffective. 42 However, a 2020 systematic review 43 demonstrated that ONS increased protein intake and serum albumin levels in older rehabilitation patients; however, the functional outcome improvements, which were reported in only a few studies, were uncertain. Therefore, supporting evidence for the use of ONS in patients with dysphagia is needed.…”
Section: Ons Interventionmentioning
confidence: 99%